1994
DOI: 10.1177/089484539402100106
|View full text |Cite
|
Sign up to set email alerts
|

Career Search Self-Efficacy: Ripe for Applications and Intervention Programming

Abstract: theory provides a valuable foundation for understanding factors related to individuals' degree of success in performing activities necessary for obtaining an occupation and/or developing a career. Briefly, self-efficacy theory postulates that the probability of engaging in an activity is determined in part by the degree to which individuals believe they can effectively perform the behavior (Bandura, 1986). To date, research in career self-efficacy has focused primarily on the relationship between selfefficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 20 publications
(23 reference statements)
0
7
0
1
Order By: Relevance
“…Internal consistency for the present sample was α = .99. An estimate of concurrent validity (r = .92; p < .01) was obtained using the Career Search Self-Efficacy Scale (CSES) (Solberg, Good, & Nord, 1994), a 35-item measure with adequate reliability and validity that assesses an individual's degree of confidence in performing a variety of career-search tasks.…”
Section: Instrumentsmentioning
confidence: 99%
“…Internal consistency for the present sample was α = .99. An estimate of concurrent validity (r = .92; p < .01) was obtained using the Career Search Self-Efficacy Scale (CSES) (Solberg, Good, & Nord, 1994), a 35-item measure with adequate reliability and validity that assesses an individual's degree of confidence in performing a variety of career-search tasks.…”
Section: Instrumentsmentioning
confidence: 99%
“…Another limitation is that our outcome variables are measured by self-administrated survey items, which may not precisely measure these psychological variables. However, it should be noted that the corresponding survey items are derived from the existing research [ 32 , 57 , 58 ]. We did not adopt all of the items, as this not only concerns barriers in terms of data collection, such as participants’ willingness to take the long survey, but also the conducting of reliability tests and factor analyses to enhance the measurement validity.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy is related to career-relevant behavior [ 29 ], and assessing self-efficacy is a very useful strategy for testing whether it affects subsequent behavior in the career area [ 30 ]. Self-efficacy theory has been provided as an important model for the study of career development [ 31 ], which has been used to understand factors related to individuals’ degree of success in performing activities necessary for following and/or developing a career [ 32 ]. In 1983, Taylor and Betz [ 33 ] introduced self-efficacy to the career decision-making process by proposing a new concept called job search self-efficacy.…”
Section: Theories and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Career self-efficacy is defined as one's perceived sense of confidence in performing tasks associated with career exploration and choice, such as self-exploration, professional search, and questioning of others (Solberg, Good, & Nord, 1994). Studies have found that low self-efficacy is linked to indecision in choosing an occupation, as expressed by switching study majors and difficulty developing a clear professional identity (Betz & Hackett, 1981).…”
Section: Self-efficacymentioning
confidence: 99%